EXPLORING MOTHER-CHILD MEMORY AS A FOUNDATION OF CHILDREN’S COGNITIVE, INTERPERSONAL AND INTRAPERSONAL INTELLIGENCE IN FILM ENOLA HOLMES (2020) - Nahdhiyah, Nahdhiyah; Junaid, Syahruni; Ariani, Nina (Elite : English and Literature Journal, 2025)
This study examines the role of mother–child memory in shaping children’s intelligence as portrayed in the film Enola Holmes (2020). Grounded in Howard Gardner’s theory of Multiple Intelligences, the research highlights how maternal memories function as a foundation for cognitive, interpersonal, and intrapersonal development. Using a qualitative content analysis approach, selected scenes involving Enola Holmes and her mother, Eudoria, were analyzed through dialogue, flashbacks, and visual codes. The findings reveal that maternal memory is not merely nostalgic, but a narrative mechanism of intellectual and emotional inheritance. Cognitively, Enola’s recollections of logic training, puzzles, and cryptographic exercises enhance her critical thinking and problem-solving skills. Interpersonally, her memories of maternal advice to empathize and understand others guide her in building trust and collaboration. Intrapersonally, memories of maternal love and encouragement foster Enola’s resilience, autonomy, and self-awareness in resisting patriarchal constraints. This research contributes to literary and film studies by demonstrating how mother–child memory functions as a transgenerational medium of intelligence formation